The Zoroastrian myth of migration from Iran and settlement in the Indian diaspora : text, translation and analysis of the 16th century Qeṣṣe-ye Sanjān 'The story of Sanjan' - Williams, Alan, 1953- (Numen Book Series, 2009)
The Qesse-ye Sanjān is the sole surviving account of the emigration of Zoroastrians from Iran to India to form the Parsi ('Persian') community. Written in Persian couplets in India in 1599 by a Zoroastrian priest, it is a work many know of, but few have actually read, let alone studied in depth. This book provides a romanised transcription from the oldest manuscripts, an elegant metrical translation, detailed commentary and, most importantly, a radical new theory of how such a text should be "read", id est not as a historical chronical but as a charter of Zoroastrian identity, foundation myth and justification of the Parsi presence in India. The book fills a lacuna that has been acutely felt for a long time.